Climate challenges: Assessing the effects of adverse temperature conditions on student absenteeism - Shahriar Kabir Shishir; Md. Rakibul Islam (Tamalanrea: Journal of Government and Development (JGD), 2025)
School absenteeism remains a persistent challenge in the education sector. This study explores the relationship between the feels-like temperature and school absenteeism in the selected schools in Trishal Upazila of Mymensingh district. Following a mixed-method design, it considers only perceived temperature variables for absenteeism and incorporates quantitative data from publicly available temperature records and daily school attendance data from school registers. Additionally, it draws insights from the qualitative inputs from teachers and education officers. Spearmen's correlation and regression analysis revealed no statistically significant relationship between feels-like temperature and school absenteeism. The Man-Whitney U test, following the summer and winter groups of months, showed that the students from secondary school are likely to be more absent during the hotter days. However, the regression coefficient tables for both schools revealed that the students from secondary schools have a tendency tobe absent more often, even when all other factors are constant. Thematic analysis from qualitative findings focused on other prominent factors, such as parental supervision, socioeconomic conditions, and administrative practices for scholarship eligibility for absenteeism. School absenteeism is less influenced by temperature factors and more influenced by structural and behavioral patterns. This study recommends targeted interventions addressing socioeconomic conditions, data manipulation, and age-specific motives. Future studies should consider a wider array of geographic coverage, focusing on climate-adverse locations and broader climatic variables.